Chinese Visceral Adiposity Index Is Associated With Incident Renal Damage in Patients With Hypertension and Abnormal Glucose Metabolism: A Longitudinal Study - Lin, Mengyue; Li, Nanfang; Heizhati, Mulalibieke; Gan, Lin; Zhu, Qing; Yao, Ling; Li, Mei; Yang, Wenbo (Frontiers in Endocrinology, 2022)
Objective: To evaluated the association between Chinese visceral adiposity index (CVAI) and incident renal damage and compared its predictive power with that of other visceral obesity indices in patients with hypertension and abnormal glucose metabolism (AGM). Methods: This retrospective cohort consecutively included patients with hypertension and AGM who did not have renal damage at baseline. Renal damage was defined using the estimated glomerular filtration rate (eGFR) and urine protein. Multivariable Cox regression analysis was used to evaluate the association between CVAI and incident renal damage. Restricted cubic splines were used to determine the shape of the association. The predictive power of the CVAI was examined and directly compared with other indices, including the VAI, body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR), using the area under the receiver operating characteristics curve (AUC) and C-index. Results: In total, 2,033 patients with hypertension and AGM were included. During a median follow-up of 2.6 years, the incidence of renal damage was 31.5, 48.9, 56.8, and 67.5/1,000 person-years across the quartiles of CVAI. Compared with the first quartile, the risk of renal damage was higher in the second (HR =1.36 [95% CI: 0.931.97]), third (HR =1.57 [95% CI: 1.092.27]), and fourth (HR =1.65 [95% CI: 1.112.44]) quartiles (P for trend =0.011). A linear dose-response association was observed. Sensitivity and subgroup analyses confirmed the robustness and consistency of the results. In terms of predictive power, the CVAI had the highest AUC and C-index values. Conclusions: CVAI is positively associated with renal damage risk in a linear dose-response pattern and has the best performance in predicting incident renal damage in patients with hypertension and AGM. The CVAI may serve as a reliable indicator for identifying patients at a high risk of renal damage.